Hemicentin-1 is an essential extracellular matrix component of the dermal–epidermal and myotendinous junctions - Daniela Welcker (Nature Portfolio, 2021)
Abstract The extracellular matrix architecture is composed of supramolecular fibrillar networks that define tissue specific cellular microenvironments. Hemicentins (Hmcn1 and Hmcn2) are ancient and very large members (> 600 kDa) of the fibulin family, whose short members are known to guide proper morphology and functional behavior of specialized cell types predominantly in elastic tissues. However, the tissue distribution and function of Hemicentins within the cellular microenvironment of connective tissues has remained largely unknown. Performing in situ hybridization and immunofluorescence analyses, we found that mouse Hmcn1 and Hmcn2 show a complementary distribution throughout different tissues and developmental stages. In postnatal dermal–epidermal junctions (DEJ) and myotendinous junctions (MTJ), Hmcn1 is primarily produced by mesenchymal cells (fibroblasts, tenocytes), Hmcn2 by cells of epithelial origin (keratinocytes, myocytes). Hmcn1 −/− mice are viable and show no overt phenotypes in tissue tensile strength and locomotion tests. However, transmission electron microscopy revealed ultrastructural basement membrane (BM) alterations at the DEJ and MTJ of Hmcn1 −/− mice, pointing to a thus far unknown role of Hmcn1 for BM and connective tissue boundary integrity.